Seroprevalence and associated risk factors of coxiella burnetii (Q fever) infection among small ruminants in selected small ruminant farms in Negeri Sembilan, Malaysia - Nur Athirah Abdurrahim (2019)
Eggs are a cheap source of protein with limited shelf life depending on storage condition s. The environmental factors such as storage time and temperature might affect the internal quality of eggs. Therefore, the objective of this study is to determine and compare the effect of storage duration and temperature on physical quality and nutritional composition of eggs from commercial and village chickens. A total of 120 eggs (commercial chicken eggs= 60, village chicken eggs= 60) were purchased and stored for O ( control), 5 and 10 days in refrigerator (4°C) and room temperature (20°C) equally. The physical qualities measured were weight loss, Haugh Unit, yolk index, albumen pH and yolk pH. Meanwhile, analysis of eggs nutritional composition such as dry matter, protein and fat were caiTied out by using proximate analysis procedure. The result showed, weight loss was increased rapidly from day O to 10 at room temperature (20°C). The Haugh unit and yolk index were decreased constantly from day O to IO at room temperature (20°C). Moreover, dry matter content decreased constantly with the increase in storage duration at room tempe rature. Ina dd i t ion, crude protein and crude fat analysis were found high nutrition content as kept longer in different storagecon d it i ons. Thus, the storage duration and temperature play an important role to preserve the quality of eggs in tenns of physical quality and nutritional composition.